2020
DOI: 10.1002/pd.5800
|View full text |Cite
|
Sign up to set email alerts
|

First‐trimester screening based on cell‐free DNA vs combined screening: A randomized clinical trial on women's experience

Abstract: Objective: To compare women's experience of first-trimester combined screening (FTCS), with women's experience of an approach that uses the combination of a detailed early anatomy scan and cell-free DNA (cfDNA) analysis. Methods: This was single-center, open label, parallel group, randomized clinical trial. Pregnant women were randomized at the time of their first prenatal visit to either a policy of first-trimester risk assessment based on FTCS, or to a policy of firsttrimester risk assessment based on ultras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…459 Cell-free DNA testing on a maternal blood sample is emerging as a non-invasive means of aneuploidy screening for foetuses with no apparent structural abnormalities although this approach currently lacks resolution in definition of sub-microscopic chromosomal anomalies. [460][461][462] [439][440][441][442]444,[454][455][456][457] and modified from ref. 458 CHD, congenital heart disease; CMA, chromosome microarray; CNV, copy number variant; ECA, extracardiac anomaly; SNV, single-nucleotide variant; WES, whole-exome sequencing; WGS, whole-genome sequencing.…”
Section: 448mentioning
confidence: 99%
See 1 more Smart Citation
“…459 Cell-free DNA testing on a maternal blood sample is emerging as a non-invasive means of aneuploidy screening for foetuses with no apparent structural abnormalities although this approach currently lacks resolution in definition of sub-microscopic chromosomal anomalies. [460][461][462] [439][440][441][442]444,[454][455][456][457] and modified from ref. 458 CHD, congenital heart disease; CMA, chromosome microarray; CNV, copy number variant; ECA, extracardiac anomaly; SNV, single-nucleotide variant; WES, whole-exome sequencing; WGS, whole-genome sequencing.…”
Section: 448mentioning
confidence: 99%
“…Routine antenatal testing on amniocentesis or CVS is focused on the identification of major chromosomal abnormalities including Trisomy 13, 18, 21 and 22q11 deletion, responsible for velocardiofacial syndrome, and should be offered to any patient pursuing invasive prenatal diagnosis without prior knowledge of cardiac or other malformations 459 . Cell‐free DNA testing on a maternal blood sample is emerging as a non‐invasive means of aneuploidy screening for foetuses with no apparent structural abnormalities although this approach currently lacks resolution in definition of sub‐microscopic chromosomal anomalies 460–462 …”
Section: Introductionmentioning
confidence: 99%
“…459 Cell-free DNA testing on a maternal blood sample is emerging as a non-invasive means of aneuploidy screening for foetuses with no apparent structural abnormalities although this approach currently lacks resolution in definition of submicroscopic chromosomal anomalies. [460][461][462] Neonates and infants requiring investigation or procedures for congenital heart disease Testing for pathogenic chromosomal CNVs by CMA or CNV seq should be performed. 434 These techniques have essentially replaced standard karyotype analysis as first line testing, although conventional karyotyping may be performed particularly in assessment of balanced translocations.…”
Section: Antenatal Testingmentioning
confidence: 99%
“…28 Migliorini et al in a randomized clinical trial of patient's experience comparing pre-and post-test survey questionnaires addressing measure reassurance, satisfaction, and anxiety between patients undergoing standard first-trimester screening (nuchal translucency and maternal serum analytes) versus ultrasound findings followed by cfDNA analysis found that mean score for reassurance was significantly higher in the cfDNA group in comparison with standard screening in both pre-and post-test questionnaires. 29 Forty women with singleton gestations were included in the study. Women were randomized at the time of their first prenatal visit to either first-trimester risk assessment based on first-trimester combined screening or first-trimester risk assessment based on sonographic findings and cfDNA.…”
Section: Dovepressmentioning
confidence: 99%
“…These authors thus concluded that first-trimester screening for fetal aneuploidy combined with detailed sonographic examination and cfDNA is associated with improved maternal satisfaction and maternal reassurance compared to the standard first-trimester combined screening with nuchal translucency (NT), and maternal serum analytes. 29 Iwarsson and Conner from the Karolinska Institute, studied detection rates and residual risk for postnatal diagnosis of an atypical chromosomal aberration after combined first-trimester screening. 30 Among 129,493 patients, 852 (0.7%) clinically significant chromosome aberrations, including those detected after birth were noted.…”
Section: Dovepressmentioning
confidence: 99%